WHO body mass index for age charts overestimate thinness and overweight compared to international and US charts applied to indigenous and non-indigenous Mexican children - Ramírez, Erik; Ramos Salas, Juan E; Barrera Bustillos, Martha; González Franco, Luis Ricardo; Flores Guillen, Elena; Pérez Jacome, Alfredo; Valencia, Mauro E (Archivos Latinoamericanos de Nutrición (ALAN), 2020)
Assessments of whether children are thin (low body mass index for age) or overweight are based on body mass index (BMI for age and sex) charts published by the World Health Organization (WHO), the International Obesity Task Force (IOTF), and the US Centers for Disease Control and Prevention (CDC). We aimed to determine whether these charts indicated different prevalence of thinness and overweight (obesity included) in indigenous and non-indigenous school aged children from different regions and ethnic groups in Mexico. A probability proportional to size, cluster sampling method was employed in four regions of the country. We recruited 1,731 children aged 7.0-9.9 (507 indigenous from six ethnic groups and 1,224 non-indigenous). BMI was calculated according to age, and thinness and overweight classifications were compared according to cutoff values in the WHO, IOTF, and CDC references. The WHO reference generated the highest rates for thinness (12.5%) and overweight (30%) in children across regions and ethnic groups. The CDC reference estimated the lowest rates of thinness in children (5.5%), and the IOTF reference estimated the lowest rates of overweight (24.7%). Estimates of both thinness (8.3%) and overweight (13.4%) rates were lower in indigenous than non-indigenous groups (14.3% and 37.5%, respectively). The WHO BMI for age chart estimated higher rates of thinness and overweight in children compared to the CDC and IOTF charts. Because thinness as indicator of undernutrition status is relatively new, differences in body composition among indigenous and non-indigenous children may justify the need for more appropriate screening criteria to compare the growth status. La clasificación del estado nutricio de los niños con delgadez o con sobrepeso se realiza empleando el índice de masa corporal (IMC para la edad y el sexo) con las tablas de la OMS, IOTF y CDC. El objetivo de esta investigación fue determinar si estas referencias resultan en diferentes prevalencias de delgadez y sobrepeso (obesidad incluida) en niños escolares indígenas y no indígenas de diferentes regiones de México. Se empleó un muestreo por conglomerados en cuatro regiones del país. Se reclutaron 1,731 niños con edades entre 7,0-9,9 (507 indígenas de cinco grupos étnicos y 1,224 no indigenas) durante 2006 y 2008. El IMC se calculó y se clasificó como delgadez y sobrepeso con los puntos de corte sugeridos por las referencias internacionales. Cuando se compararon las clasificaciones, la referencia de OMS generó la prevalencia más alta de delgadez (12,5%) y sobrepeso (30%) en niños de todas las regiones y grupos étnicos. La referencia de los CDC estimó las prevalencias más bajas de delgadez (5,5%) y la referencia IOTF produjo las proporciones más bajas de sobrepeso (24,7%). Las proporciones de delgadez (8,3%) y sobrepeso (13,4%) fueron más bajas en niños indígenas que en los no indígenas (14.3% y 37.5%, respectivamente). La referencia de la OMS del IMC para la edad produjo las prevalencias más altas de delgadez y sobrepeso en comparación con los estándares de CDC y IOTF. Dado que la delgadez como indicador de desnutrición en niños es de uso reciente, las diferencias encontradas entre indígenas y mestizos pueden justificar el contar con mejores herramientas de tamizaje en estudios de crecimiento.